2002
DOI: 10.1177/030089160208800206
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Breast and Colon Cancer Long-term Survivors: An Assessment with the Eortc Qlq-c30 and Sf-36 Questionnaires

Abstract: Our study supports the hypotheses that the impact of cancer on quality of life over a period of time is not necessarily devastating in survivors. As regards the impact of different medical strategies, although our data are consistent with other research supporting the hypotheses that hormone therapy does not cause a decrease in long-term quality of life, differences we observed between hormone and chemotherapy might be caused by the action of confounds we were not able to control for or by the distortion intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 28 publications
6
38
1
6
Order By: Relevance
“…In a cross-sectional study, these variables were included as factors to predict the Cancer Rehabilitation Evaluation System Global Score three years on average following colon surgery [3]. Recently, comorbidity was reported to show an impact on various QOL scales according to QLQ-C30 [5]. Ramsey et al [4] reported also in cross-sectional study that only low income status was associated with worse outcomes for various dimensions of QOL according to the Functional Assessment of Cancer Therapy Scales for Colorectal Cancer (FACT-C) and the Health Utilities Index (HUI).…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study, these variables were included as factors to predict the Cancer Rehabilitation Evaluation System Global Score three years on average following colon surgery [3]. Recently, comorbidity was reported to show an impact on various QOL scales according to QLQ-C30 [5]. Ramsey et al [4] reported also in cross-sectional study that only low income status was associated with worse outcomes for various dimensions of QOL according to the Functional Assessment of Cancer Therapy Scales for Colorectal Cancer (FACT-C) and the Health Utilities Index (HUI).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, researchers and clinicians are increasingly aware of the importance of QOL issues among long-term cancer survivors (Bloom, 2002;Dorval et al, 1998;Ganz, 2001;Ganz et al, 2002;Gotay and Muraoka, 1998;Moinpour et al, 1989;Mosconi et al, 2002;Nayfield et al, 1992). Differentiated QOL assessments such as that provided by the QLACS can help identify longterm sequelae that clinicians should monitor, and can identify areas where particular persons need services or interventions.…”
Section: Long-term Cancer Survivorsmentioning
confidence: 99%
“…This has led to interest in long-term QOL among cancer survivors (Bloom, 2002;Deimling et al, 2002;Ganz et al, 2002Ganz et al, , 1998Gotay and Muraoka, 1998;Schag et al, 1994;Tomich and Helgeson, 2002). Also promoting interest in longterm QOL is evidence that cancer treatments themselves may have long-term physical effects that can adversely influence QOL (American Society of Clinical Oncology, 1996;Bloom, 2002;Deimling et al, 2002;Dorval et al, 1998;Ganz, 2001;Ganz et al, 2002;Gotay and Muraoka, 1998;Moinpour et al, 1989;Mosconi et al, 2002;Nayfield et al, 1992;Steer et al, 2002;Tomich and Helgeson, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction is also high in patients kept under surveillance by general practitioners or surgeons, and no difference in quality of life is seen between the two [106] . Mental wellbeing has, however, been reported to be high in survivors of colorectal cancer, and there is evidence that any form of surveillance has little impact in terms of psychological benefit [107][108][109] .…”
Section: Who Should Undertake Follow-up?mentioning
confidence: 99%